The Research Skills, Personal Effectiveness, Networking and Team Working, and Communication Skills of Polytechnic University of the Philippines Laguna Campuses Faculty: Basis for an Action Plan - Pambuena, E L; Bernarte, R (KnE Social Sciences, 2018)
This study aimed to assess the Research Skills, Personal Effectiveness, Networking and Teamworking, and Communication Skills of Polytechnic University of the Philippines Laguna Campuses Faculty. This included both the regular and part time faculty members of PUP-LGU Campuses in Laguna The study utilized the quantitative research method and the descriptive type of research. The 94 respondents of the study were randomly chosen from 184 Regular and Part Time faculty members of PUP-LGU Campuses in the Province of Laguna for School Year 2016-2017. The researcher used the questionnaire and made personal interviews to randomly selected faculty members. The data gathered were tabulated through the form of frequency percentage distribution, percentage, T test, and One-Way ANOVA. Based on the findings, it was concluded that the respondents have a consensus that they are able to practice and demonstrate relevant research skills, they are able to work harmoniously and emphatically with their network and respective team in a collaborative effort. Thus, it was recommended that those teachers who are in their early years of teaching must be given support in terms of research training that will supplement the need to demonstrate research efficacy even though they are still learning their way through their academic career. Moreover, all the faculty must undergo a relevant research training to properly gauge the competency needed. For instance, LGU funded campuses may embark a collaborative research undertaking that will foster research culture among the campuses, develop a local campus research agenda in line with the university research and implement the action plan that will develop the research efficacy of the faculty members with required outputs as demonstrated in the attached proposed action plan. Keywords: Research Skills, Personal Effectiveness, Networking and Teamworking, Communication Skills